AN INNOVATION FROM DURIAN (TEMPOYAK) TO SEASONING PASTE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 6 December 2016 – A group of students from the Universiti Sains Malaysia (USM) School of Industrial Technology has made an innovation by using Durian (Tempoyak) to make seasoning paste.